A defined diet for pre-adult Drosophila melanogaster - Felipe Martelli; Annelise Quig; Sarah Mele; Jiayi Lin; Tahlia L. Fulton; Mia Wansbrough; Christopher K. Barlow; Ralf B. Schittenhelm; Travis K. Johnson; Matthew D. W. Piper (Scientific Reports, 2024)
Abstract Drosophila melanogaster is unique among animal models because it has a fully defined synthetic diet available to study nutrient-gene interactions. However, use of this diet is limited to adult studies due to impaired larval development and survival. Here, we provide an adjusted formula that reduces the developmental period, restores fat levels, enhances body mass, and fully rescues survivorship without compromise to adult lifespan. To demonstrate an application of this formula, we explored pre-adult diet compositions of therapeutic potential in a model of an inherited metabolic disorder affecting the metabolism of branched-chain amino acids. We reveal rapid, specific, and predictable nutrient effects on the disease state consistent with observations from mouse and patient studies. Together, our diet provides a powerful means with which to examine the interplay between diet and metabolism across all life stages in an animal model.